Measurements of Radon Concentrations in Some Dried Fruit and Grain Samples by (CR-39) Nuclear Track Detector - Jameel, Athraa Naji (Iraqi Journal of Science, 2022)
The purpose of this study was to measure the radon concentration of some dried fruit and grain samples which were consumed as a meal. This is performed by counting the alpha tracks emitted from radon by exposing the CR-39 detector. Measurements indicated that the highest concentration of radon in dried fruit samples was in dried coconut sample 69.89247 Bq/m3, and the lowest concentration of radon was in figs 50.40323 Bq/m3, while the highest concentration of radon was in grain samples in oats was 61.82796 Bq/m3, The lowest concentration of radon was in Iraqi bulgur was 48.3871 Bq/m3, These results are due to the type and characteristics of the soil. Also shows that the behavior of the surface exhalation rate is higher than the mass exhalation rate.The concentration of radon gas and the rate of exhalation of radon for samples of Dehydrated fruit and cereals are within the permissible global limit, and eating these foods will be healthy and safety for the public.